Metabolic therapy in cardiology from the perspective of evidence-based medicine - V. I. Kostin; O. A. Shangina; V. G. Shelikhov (Фундаментальная и клиническая медицина)
Over the past few decades, various applications of the metabolic drugs have been extensively tested. Most of them affect oxygen-dependent processes, improving cellular metabolism and increasing tissue resistance to hypoxia and ischemia. The most promising candidates include components of the respiratory chain, purine nucleosides, and creatine phosphate which affect glucose oxidation and fatty acid metabolism in the Krebs cycle. This review critically evaluates the most popular drugs of this group (adenosine triphosphate, adenosine-5-monophosphate, creatine phosphate, coenzyme Q10, cytochrome C, adenosine, glucose-insulin-potassium solution, L-carnitine, mildronate, and trimetazidine), which are widely represented on the pharmaceutical market. Of all metabolic drugs, only trimetazidine was included in the European and Russian recommendations for the second-line treatment of stable angina. In most clinical studies, the therapeutic efficacy of metabolic drugs has been evaluated using the surrogate endpoints. Despite being actively advertised and widely used in the clinical practice, metabolic drugs currently do not have a convincing evidence base for affecting prognosis (mortality and/or major adverse cardiovascular events). Further studies in large-scale randomised trials are needed to confirm the beneficial effects of the metabolic drugs in cardiovascular medicine.